1973
DOI: 10.1002/bjs.1800600323
|View full text |Cite
|
Sign up to set email alerts
|

Primary adenocarcinoma arising in a vitello-intestinal duct remnant at the umbilicus

Abstract: A case is presented of a primary adenocarcinoma which arose from a vitello‐intestinal duct remnant at the umbilicus in a 46‐year‐old woman. The incidence, diagnosis, and management of these unusual tumours are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Remnants of small intestinal mucosa, ectopic gastric mucosa, and mixed type with colonic mucosa are reportedly seen in 62.5%, 32.5%, and 12.5% of the cases of umbilical cyst, respectively [5]. Adenocarcinoma can also rarely occur if resection leaves behind residual tissues [6]. In addition, ensuring complete resection of the umbilical cyst reduces the risk of postoperative umbilical drainage or surgical infection.…”
Section: Discussionmentioning
confidence: 97%
“…Remnants of small intestinal mucosa, ectopic gastric mucosa, and mixed type with colonic mucosa are reportedly seen in 62.5%, 32.5%, and 12.5% of the cases of umbilical cyst, respectively [5]. Adenocarcinoma can also rarely occur if resection leaves behind residual tissues [6]. In addition, ensuring complete resection of the umbilical cyst reduces the risk of postoperative umbilical drainage or surgical infection.…”
Section: Discussionmentioning
confidence: 97%
“…A literature review revealed no reports of MD adenocarcinoma with an umbilical side of VDR or a huge cystic lesions; our case is therefore considered to be the first one. As for the E type, which occurs in the abdominal wall of the umbilicus, only two cases have been reported [ 8 , 9 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80% of these are metastatic to umbilicus (Sister Marry Joseph Nodule), and primary tumor representing for 20% at this location 5 . A primary adenocarcinoma arising at the umbilicus is very rare 3 . Adenocarcinoma represents over half of these reported cases 6 .…”
Section: Discussionmentioning
confidence: 99%
“…In our case possibility of urachus tumor is ruled out, as these tumors are found below the umbilicus, commonly related to micturition and at the time of presentation suprapubic mass is palpable in around 80% of cases. Glazer et al reported primary adenocarcinoma at umbilicus in a 46 year old female, arose from a vitello-intestinal duct remnant, (also gave two sites of origin) a primary adenocarcinoma at this site can only arise from a pre-existing endometioma or an embryological remnant 3 . Metastasis from the umbilicus is a simpler phenomenon than metastasis to the umbilicus, considering lymphatics of the abdominal wall 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation